Clinicopathological characteristics of individuals with coexisting melanoma and chronic lymphocytic leukaemia: a multicentre cohort study. (9th September 2022) - Fisher, Rachel Mary; Ji‐Xu, Antonio; Abbott, Rachel; Basu, Tanya; Brown, Alistair; Foley, Catherine; Glen, Catriona; Gupta, Girish; Hasan, Zeeshaan; Ismail, Ferina; Khalid, Amina; Khoo, Andre B. S.; et al.
Abstract: Background: Individuals with a prior diagnosis of chronic lymphocytic leukaemia (CLL) have a higher risk of developing melanoma and exhibit poorer outcomes than patients without CLL. However, there are limited data reporting the clinicopathological features of melanoma diagnosed in patients with CLL. Aims: To review clinicopathological characteristics of patients with coexisting diagnoses of melanoma and CLL. Methods: A retrospective review was undertaken for patients with coexisting diagnoses of melanoma and CLL between 2005 and 2015 in 11 centres in the UK and Ireland. Results: Overall, 46 cutaneous melanomas identified in 45 patients were included. In 28 (62.2%) patients, melanoma was diagnosed after an existing diagnosis of CLL. In this group, mean Breslow thickness was 2.7 mm (range 0.2–25 mm). Ten patients (35.7%) developed locoregional recurrence and 8 (28.6%) developed distant metastases. Melanoma‐specific mortality was 5 of 28 (17.9%) and all‐cause mortality was 13 of 28 (46.4%). In 17 patients, melanoma was diagnosed before CLL. In this group, mean BT was 2.9 mm (range 0.4–14 mm); five patients (29.4%) developed locoregional recurrence and three (17.6%) developed distant metastases. Melanoma‐specific mortality was 1 of 17 (5.8%) and all‐cause mortality was 5 of 17 (29.4%) in this group. Conclusions: To our knowledge, this is the first and largest cohort study to report clinicopathological data of coexisting melanoma and CLL in the UK and Ireland. Although the thickness of primary melanoma was not different before or after a CLL diagnosis, melanoma recurrence and melanoma‐specific mortality appear to be more common in patients with a prior diagnosis of CLL.